Staphylococcus aureus colonization on antecubital non-exacerbated atopic dermatitis patient compared to healthy children - Nur Khamidah; Evy Ervianti; Hari Sukanto (PAGEPress Publications, 2019)
Atopic dermatitis is chronic pruritic inflammatory skin disease affects one third of children in the world, and the highest number of child`s skin problems in Indonesia. The complex role of the skin microbiome in the pathogenesis of atopic dermatitis is being elucidated. Interaction between skin barrier defects, and immunological factors can change the skin microbiome, and increased Staphylococcus aureus colonization. The aim of this study was to compare the colony of Staphylococcus aureus from antecubital fossa of non-exacerbated atopic dermatitis children to healthy children without history of atopic dermatitis. A comparative observational analytic with cross sectional design, examined antecubital swab culture from 17 non-exacerbated atopic dermatitis patients and 17 controls to investigate the presence of Staphylococcus aureus and density of the colonization. Staphylococcus aureus skin colonization was seen in 5 patients (29.41%) in non-exacerbated atopic dermatitis patients but none in control group (statistically significant with p=0.044), relative risk 2.417. All of positive colonization revealed moderate and heavy bacterial growth (104->105 cfu/cm2). This finding supports previous study that atopic dermatitis prone to colonized with Staphylococcus aureus.